Rancang Bangun Mesin Penggiling Sambel Pecel sebagai Solusi Teknologi Tepat Guna bagi Pelaku Usaha Kecil - Rifki Juniar Pratama; Virana Marhaeni Maerah Devi Imam Putri; Fajar Ardian Nur Alif; Rina Devi Azizah; Zulfarhy Abuhasmy; Angga Dutahatmaja (Yayasan Cendekia Gagayunan Indonesia, 2025)
This community service aims to design and build a sambel pecel grinding machine as an appropriate technological solution for small business actors. Small businesses, especially pickle sauce producers, often face obstacles in the production process which are still manual and require considerable time and effort. Through a technological engineering approach, this activity produces a prototype of a grinding machine that is efficient, easy to operate, and in accordance with the needs of micro-scale business actors. The implementation method includes surveying partner needs, designing machine designs, manufacturing units, and functional trials in the field. The results of the activity show that this machine is able to increase production capacity up to 3 times compared to manual methods, reduce work fatigue, and improve the consistency of texture and taste of sambel pecel. In addition, service partners receive training on the use and maintenance of machines, so that the sustainability of their use can be maintained. This innovation is expected to be a model for the application of other appropriate technologies in supporting the independence and productivity of small business actors in the traditional food sector.